Kegiatan peningkatan pengetahuan dan kemampuan kesiapsiagaan darurat bencana di Pondok Pesantren - Lutfiya, Indah; Damayanti, Ratih; Tyas, Anestasia Pangestu Mei; Dwicahyo, Herman Bagus; Rohmah, Shofiyatur; Ibad, Mursyidul (JOURNAL of Public Health Concerns, 2025)
Background: Islamic boarding schools (pesantren), as boarding Islamic educational institutions, play a strategic role in shaping the character of their students (students). However, they face serious challenges related to disaster risks, particularly earthquakes and fires, due to overcrowding and a lack of mitigation systems. Jabal Noer Islamic Boarding School in Sidoarjo, located in an earthquake-prone zone and home to hundreds of teenage students, exhibits low levels of emergency preparedness, including first aid knowledge and skills. Given this high vulnerability, educational interventions in the form of emergency response and first aid training involving the entire Islamic boarding school community are needed to strengthen disaster response capacity and create a safe and prepared learning environment. Purpose: To improve the knowledge and skills of students within Islamic boarding schools in disaster preparedness in the face of emergencies. Method: The activity was held on July 21, 22, and 23, and August 2, 2025, at the Jabal Noer Islamic Boarding School, Geluran Taman, Sidoarjo Regency, East Java. Twenty-six participants, consisting of students and one security guard, were involved. The material was delivered through focus group discussions (FGDs) between D4 K3 lecturers and the boarding school administrators, who also formed the SIGAP cadre. Knowledge and skills were measured using a questionnaire, assessing participants' attendance, practical simulation skills, and students' socio-cultural involvement in the boarding school environment. A descriptive and quantitative evaluation was conducted by assessing the level of change in knowledge and skills before and after the educational activities (pre-test) and after the educational activities (post-test). Results: Data obtained showed that the level of knowledge and skills of participants before the educational activities (pre-test) achieved an average score of 24.8 points with a standard deviation of 16.86, while the level of knowledge and skills of participants after the educational activities (post-test) achieved an average score of 74.0 points with a standard deviation of 16.07. The intervention improved participants' ability to practice basic skills such as cardiopulmonary resuscitation and minor injury management. The intervention also successfully formed SIGAP cadres and provided safety facilities, which overall strengthened the preparedness of the Islamic boarding school environment. Conclusion: This community service activity successfully increased disaster preparedness capacity through the formation of SIGAP cadres and first aid training. The increased knowledge and skills of SIGAP cadres also made a positive contribution and strengthened the institution in disaster response, injury management, earthquake and fire preparedness, and disaster impact prevention. Suggestion: SIGAP cadres are expected to conduct routine training and periodic simulations. It is also hoped that educational activities and training in disaster preparedness can be integrated into the extracurricular curriculum through collaboration with external institutions such as the Indonesian Red Cross and the Regional Disaster Management Agency. Keywords: Disaster; Emergency preparedness; First aid; Islamic boarding schools Pendahuluan: Pondok pesantren sebagai lembaga pendidikan Islam berasrama memiliki peran strategis dalam pembentukan karakter santri, namun menghadapi tantangan serius terkait risiko bencana, khususnya gempa bumi dan kebakaran, akibat kepadatan hunian dan minimnya sistem mitigasi. Pondok Pesantren Jabal Noer di Sidoarjo, yang berada di zona rawan gempa dan dihuni oleh ratusan santri remaja, menunjukkan rendahnya kesiapsiagaan darurat, termasuk pengetahuan dan keterampilan pertolongan pertama. Mengingat tingginya kerentanan tersebut, diperlukan intervensi edukatif berupa pelatihan tanggap darurat dan P3K yang melibatkan seluruh komunitas pesantren guna memperkuat kapasitas respon bencana, dan menciptakan lingkungan belajar yang aman dan siaga. Tujuan: Untuk meningkatkan pengetahuan dan kemampuan kesiapsiagaan bencana pada santri di lingkungan Pondok Pesantren dalam menghadapi darurat bencana. Metode: Kegiatan dilaksanakan pada 21, 22, 23 Juli dan 2 Agustus 2025 di Pondok Pesantren Jabal Noer, Geluran Taman, Kabupaten Sidoarjo, Jawa Timur. Melibatkan 26 peserta yang terdiri dari santri dan satu petugas keamanan Pondok Pesantren. Materi disampaikan melalui focus group discussion (FGD) antara Dosen D4 K3 dan pengasuh pondok pesantren yang sekaligus membentuk kader SIGAP. Pengukuran tingkat pengetahuan dan kemampuan menggunakan media kuesioner dengan memberikan penilaian dari aspek kehadiran peserta, keterampilan praktis simulasi, dan keterlibatan sosial budaya santri di lingkungan pesantren. Sebagai evaluasi secara deskriptif dan kuantitatif adalah dengan melihat tingkat perubahan pengetahuan dan kemampuan sebelum kegiatan edukasi (pre-test) dan sesudah kegiatan edukasi (post-test). Hasil: Mendapatkan data bahwa tingkat pengetahuan dan kemampuan peserta sebelum kegiatan edukasi (pre-test) mendapatkan rerata skor 24.8 poin dengan standar deviasi 16.86, sedangkan tingkat pengetahuan dan kemampuan peserta sesudah kegiatan edukasi (post-test) mendapatkan rerata skor 74.0 poin dengan standar deviasi 16.07. Meningkatkan kemampuan peserta dalam mempraktikkan keterampilan dasar seperti resusitasi jantung paru dan penanganan cedera ringan. Intervensi juga berhasil membentuk kader SIGAP dan menyediakan fasilitas keselamatan, yang secara keseluruhan memperkuat kesiapsiagaan lingkungan pesantren. Simpulan: Kegiatan pengabdian masyarakat ini berhasil meningkatkan kapasitas kesiapsiagaan bencana melalui pembentukan kader SIGAP dan pelatihan pertolongan pertama (P3K). Meningkatnya pengetahuan dan kemampuan kader SIGAP juga memberikan kontribusi yang positif dan memperkuat institusi dalam menghadapi bencana, penanganan cedera, potensi gempa, kebakaran dan pencegahan dampak bencana. Saran: Diharapkan kader SIGAP melakukan pelatihan rutin dan simulasi berkala. Diharapkan juga kegiatan edukasi dan pelatihan kesiapsiagaan tanggap darurat bencana dapat di integrasikan ke dalam kurikulum ekstrakurikuler dengan melakukan kolaborasi pada lembaga eksternal seperti PMI dan BPBD.